Exploring the Relationship between Village Head Leadership Styles and Community Engagement in Village Education - Dwi Suharnoko (AL-ISHLAH: Jurnal Pendidikan, 2025)
Community participation is critical for the success of village education programs, particularly in rural areas. However, the role of village head leadership styles in shaping such participation remains underexplored. This study investigates how different leadership styles—particularly participatory, transformational, and authoritarian—influence community engagement in education initiatives at the village level. A mixed methods approach was employed using an exploratory-sequential design. The qualitative phase involved semi-structured interviews and focus group discussions with village heads, officials, and residents from six villages. The findings from this phase informed the design of a structured survey, which was distributed to 150 respondents across diverse village settings. Quantitative data were analyzed using correlation and regression techniques. The study found that participatory leadership is strongly associated with higher levels of community involvement in village education programs. Villages led by participatory or transformational leaders demonstrated more inclusive planning and stronger program ownership. Conversely, authoritarian leadership correlated with lower participation rates. Socio-economic conditions were found to moderate these relationships; for example, economically disadvantaged villages showed lower participation even under participatory leadership. These results highlight the effectiveness of participatory leadership in fostering educational engagement but also underscore the influence of contextual factors such as income levels and cultural norms. The study confirms that leadership style alone is insufficient without parallel support structures. Leadership development strategies emphasizing inclusivity and empowerment are essential for improving education outcomes in rural communities. Future programs should integrate leadership training with socio-economic support mechanisms.